Performance characteristics of TOP5 versus NON-TOP5 races in female professional cycling - van Erp, T.; Lamberts, R. P. (International Journal of Sports Physiology and Performance, 2022)
Introduction: Maximal mean power output (MMP) is commonly used to describe the demands and performances of races in professional male cycling. In the female professional cyclist domain, however, there is limited knowledge regarding MMPs in races. Therefore, this study aimed to describe MMPs in female professional cycling races while investigating differences between TOP5 and NOT-TOP5 races. Methods: Race data (N = 1324) were collected from 14 professional female cyclists between 2013 and 2019. Races were categorized as TOP5 or NOT-TOP5. The MMPs were consequently determined over a range of different time frames (5 s to 60 min). To provide these MMPs with additional context, 2 factors were determined: when these MMPs were attained in a race (based on duration and kilojoules spent [kJspent·kg-1]) and these MMPs relative to the cyclist`s season`s best MMP (MMP%best). Results: Short-duration power outputs (=1 min) were higher in TOP5 races compared with NOT-TOP5 races. In addition, the timing (both duration and kJspent·kg-1) of all MMPs was later and after more workload in the race in TOP5 compared with NOT-TOP5 races. In contrast, no difference in MMP%best was noted between TOP5 and NOT-TOP5 races. Conclusions: TOP5 races in female cycling are presented with higher short-duration MMPs (=1 min) when compared with NOT-TOP5 races, and cyclists were able to reach a higher percentage of their seasonal best MMP when they were able to finish TOP5. In addition, these MMPs are performed later and after more kJspent·kg-1 in TOP5 versus NOT-TOP5 races, which confirms the importance of "fatigue resistance" in professional (female) cycling.